Late diagnosis of HIV infection in a center from the metropolitan area of Buenos Aires (Actualizaciones en Sida e Infectología, 2025)
Background: Late diagnosis of HIV is defined as a CD4 + T cell count below 350/mm3 and/or associated with a WHO stage 2 opportunistic event. Advanced disease represents the subgroup of people with counts below 200 CD4 + T lymphocytes/mm3 and/or with WHO stage 3 and 4 events. In Argentina, 45% of new HIV diagnoses are late, including 29% of patients with advanced disease. This work was carried out to characterize HIV late diagnosis during the period 2018-2021 in a reference center in the Buenos Aires Metropolitan Area (BAMA), Argentina.Patients and methods: Descriptive, observational, cross-sectional study that included people over 18 years of age with a diagnosis of HIV infection (PLHIV) between January 1, 2018, and December 31, 2021.Results: 1116 PLHIV were included, of which 50% (n= 558) had late diagnosis and 27% (n= 301) had advanced disease. Thirty percent (n= 90) of people with advanced disease had an opportunistic event, the most frequent being Pneumocystis jirovecii pneumonia, tuberculosis and esophageal candidiasis.Conclusions: The late diagnosis of HIV infection continues to be a frequent problem, representing half of new HIV diagnoses in our center. It is necessary to implement actions to improve access to diagnosis and ART.
Keywords: HIV, late diagnosis, advanced disease, opportunistic events, BAMA